Underspecification and low vowel harmony in Okpe - Douglas Pulleyblank (LibraryPress@UF, 1986)
This paper examines the effect of [ATR] vowel harmony on low vowels in Okpe, an Edoid language of Nigeria. The relevant facts can be summarized as follows: Low vowel stems condition [-ATR] forms on affixes. Low vowel affixes surface as [+low] in [-ATR] contexts and as [-low] when in [+ATR] contexts. Of particular interest is the additional fact that an underlyingly low vowel surfaces as [-low], [-ATR] in certain [+ATR] environments. To explain these alternations, it will be argued that low vowels are underlyingly unspecified for vocalic features. Redundancy rules, supplied for the most part by Universal Grammar, interact with the vowel harmony system and rules of syllabification to derive the non-low variants of under1yingly low vowels. By positing underspecified forms, it will be shown that no ad hoc rules need to be stipulated.